The Effect of Hand Paddle and Push Up Exercises to Increase Swimming Speed in Children Aged 11-12 Years - Rakafadni Historian; Dewi Susilawati; Respaty Mulyanto (UNIB Press, 2024)
This study aims to determine how influential the use of Hand Paddle media and Push Up Exercises are to increase freestyle swimming speed in children aged 11-12 years. This study used Quantitative research methods and Experimental research types, Freestyle swimming test using one-group pre-test post-test design for 10 treatments, This study was as many as 20 students from extracurricular swimming at SDN Pasir benteng 2 with Purposive Sampling sampling technique, The results of descriptive analysis showed a significant decrease in swimming time for both groups. The average swimming time of the Hand Paddle group decreased from 35.66 seconds in the Pre Test to 29.82 seconds in the Post Test, while the Push Up group decreased from 37.41 seconds to 35.35 seconds, These findings suggest that both interventions have been successful in increasing swimming speed.